Constructing A Smart City Brand Identity: The Case of South Tangerang - Salamah, Ummi; Yananda, Muhammad Rahmat (JURNAL KOMUNIKASI INDONESIA, 2018)
Cities and urban regions have become centers of innovation since the Industrial Revolution and they continue to be so in the realm of Digital Revolution, using the concept of the smart city which combines modern ICT infrastructure with economic growth, high quality of life, wise natural resources management as well as investment in human and social capital through participatory government. Employing two (2) approaches, namely: (1) construction of regional competitiveness; and (2) place branding, this paper analyze South Tangerang city brand identities constructed via stakeholders’ direct experiences and official documents based on the smart city attributes and indicators coined by Nam & Pardo (2011). The study constructed data gathered from desk research and semi-structured interviews with 19 informants representing quadruple helix. The results showed that South Tangerang has strong points in the human dimension of a smart city but still need improvements in technology and institution dimension. Identities constructed from its stakeholders' perception and secondary data indicate that South Tangerang is an urban area dan has a basis for a knowledge-based economy.